Hubungan Hipertensi dengan Life Style pada Pasien Penyakit Jantung Koroner di Rumah Sakit Wulan Windy - Ani Rahmadhani Kaban; Dedi Dedi; Agus Surya Bakti; Irawati Sibagariang (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertension is a strong and important risk factor for cardiovascular diseases and kidney diseases, such as coronary heart disease, heart failure, and kidney failure. High blood pressure can be influenced by genetic factors, environmental factors and the interaction between the two factors.This study aims to determine the relationship between hypertension and lifestyle in coronary heart disease patients at Wulan Windy Marelan General Hospital in 2024.The research design used in this study uses an analytical survey method with a cross-sectional approach. This study was conducted at the Heart Polyclinic of Wulan Windy Marelan General Hospital, Medan in 2024. The population in this study were coronary heart patients totaling 4676 respondents from December 2023-February 2024. The sampling technique used was purposive sampling with reference to the Slovin formula, namely 100 respondents. The data collection instrument used univariate and bivariate analysis. The test used was the Chi-Square test. Research results Based on statistical tests using the chi-square test, the p-value = (0.038) (α = <0.05) is obtained, which is less than or not more than α = 0.05, which means that Ho is rejected, Ha is accepted, which means that there is a significant relationship between hypertension and lifestyle in coronary heart disease patients at Wulan Windy Marelan General Hospital in 2024.The conclusion in this study shows that statistically there is a relationship between hypertension and lifestyle in coronary heart disease patients at Wulan Windy Marelan General Hospital in 2024.